Pengaruh Brand Awareness dan Perceived Quality Terhadap Purchase Intention Dengan Brand Trust Sebagai Variabel Mediasi Pada Skincare Avoskin - Aldwi Nartima Putriana; Abdurrahman Abdurrahman (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
This study will look at the extent to which Avoskin products can form positive brand awareness, perceived quality, and brand trust in the minds of consumers, and how this affects purchase intentions for brands that have been marketed. This study involves all individuals who intend to make purchases on Avoskin skincare products as a population. Based on the results of the analysis, it is known that the Brand Awareness variable has a positive effect on Brand Trust, the results of Perceived Quality also have a positive effect on Brand Trust, and Brand awareness has no positive effect on Purchase Intention, then Perceived Quality has a positive effect on Purchase Intention, then Brand trust has a positive effect on purchase intention, and there is Brand Awareness has no influence on Purchase Intention through Brand Trust. The final finding is that Perceived Quality does not have a positive influence on Purchase Intention through Brand Trust. The purposive sampling technique was used for sample selection in this study so that the number of respondents taken as samples was 130 using the SEM analysis method. These criteria include individuals who already know Avoskin skincare products, aged at least 17 years. The managerial implications of this research are expected to build Avoskin skincare for the better that brand awareness, perceived quality, and brand trust significantly affect purchase intention, Avoskin skincare companies can improve their marketing strategies to increase brand awareness, perceived quality, and consumer trust, which in turn can increase sales of their products.